Scalable polymer-based ferrite composites with matching permeability and permittivity for high-frequency applications - Wang, Y; Edwards, E; Hooper, I; Clow, N; Grant, P (Springer Verlag, 2015)
© 2015, © Crown Copyright, Defence Science and Technology Laboratory UK. Materials with relatively high and equal permeability and permittivity are promising for applications in telecommunications, but so far, few practical candidates have been identified. In this work, functional composites consisting of epoxy resin and Ni0.4Zn0.6Fe2O4 ferrite particles have been fabricated by a scalable and flexible casting route. It has been experimentally demonstrated that at frequencies in the 100 MHz range, the composite with ferrite loading of 53 vol% can achieve broadband impedance matching to free space with a refractive index of approximately 6, giving <0.03 % reflection and over 96 % transmission of incident radiation. These results indicate a more flexible route to the fabrication of impedance-matched materials for antenna miniaturization, which has been demonstrated by the casting of the impedance-matched composite into hemispheres suitable for electrically small antennas.